Differential diagnosis of relapsing polychondritis from asthma by 18‐fluoro‐2‐deoxyglucose positron emission tomography and computed tomography. Issue 4 (12th February 2021) - Ono, Mariko; Maeda, Yuki; Koyama, Nobuyuki; Nakamura, Hiroyuki; Aoshiba, Kazutetsu
Abstract: About a half of all patients with relapsing polychondritis show airway involvement, which is a major cause of morbidity and mortality from this disease. FDG‐PET/CT is useful in the differential diagnosis of relapsing polychondritis from asthma. Abstract : About a half of all patients with relapsing polychondritis show airway involvement, which is a major cause of morbidity and mortality from this disease. FDG‐PET/CT is useful in the differential diagnosis of relapsing polychondritis from asthma.